PTPN22 C1858T polymorphism in Colombian patients with autoimmune diseases (2005)
A functional single nucleotide polymorphism (SNP) C1858T in the protein tyrosine phosphatase nonreceptor 22 (PTPN22) gene encoding an intracellular phosphatase with negative regulatory effects on T-cell activation is associated with some autoimmune diseases in Caucasians. Taking into account firstly, that SNP frequencies may vary across populations and, secondly, that replication studies are important to confirm previous associations, we examined the influence of PTPN22 polymorphism in 621 Colombian patients with four autoimmune diseases. Accordingly, 298 patients with rheumatoid arthritis (RA), 143 with systemic lupus erythematosus (SLE), 70 with primary Sjogren's syndrome (pSS) and 110 with Type 1 diabetes (T1D) were studied. The control group consisted of 308 matched healthy individuals. Genotyping of PTPN22 was performed by the real-time polymerase chain reaction technology, using the TaqMan 5?-allele discrimination assay. The 1858 T allele was found to be a risk factor for pSS (odds ratio (OR)=2.42), SLE (OR=2.56), and T1D (OR =1.83). A lower but nonsignificant trend was observed for RA (OR=1.26). These results confirm the influence of PTPN22 in autoimmunity and indicate that autoimmune phenotypes could represent pleiotropic outcomes of nonspecific disease genes that underlie similar immunogenetic mechanisms. © 2005 Nature Publishing Group. All rights reserved.